Islam - Gordon, Matthew (New York, NY Facts on File, 1991)
An overview of Islam chronicling the religion's impact historically and in the modern world and discussing its origins, basic beliefs, structure, places of worship, and rites of passage.
Includes bibliographical references (p. 126) and index.
Keywords: Islam -- Juvenile literature; Islam